Diffusion-Weighted Imaging Findings of Ischemic Spinal Injury in a Chondrodystrophic Dog With Fibrocartilaginous Embolism - Yun, Taesik; Lee, Kang-Il; Koo, Yoonhoi; Kim, Hakhyun; Chang, Dongwoo; Lee, Chulhyun; Yang, Mhan-Pyo; Kang, Byeong-Teck (Frontiers in Veterinary Science, 2020)
A 9-year-old, intact male Shih-tzu dog presented with systemic weakness and a peracute onset of tetraplegia. Tetraplegia, with lower motor neuron signs, was noted upon neurological examination. Diseases that cause acute flaccid tetraparesis, such as acute fulminating myasthenia gravis, polyradiculoneuritis, tick paralysis, and botulism, were ruled out based on history, normal electrophysiological tests, and non-response to the neostigmine challenging test. Initial 0.3-Tesla (T) magnetic resonance imaging (MRI) findings included sharply demarcated intramedullary lesions at the C3-C6 level, mainly involving gray matter, which appeared hypo- to iso- intense on T1-weighted images (WIs), and hyperintense on T2-WIs and fluid-attenuated inversion recovery images. There was no enhancement on post-contrast T1-WIs. Neutrophilic pleocytosis was observed in the cerebrospinal fluid analysis. No clinical responses were observed for the treatment of noninfectious myelitis with an immunosuppressive dosage of prednisolone. A follow-up 3-T MRI 6 days later demonstrated hyperintensity on diffusion-WI (DWI) and a decreased apparent diffusion coefficient (ADC) value (0.54 × 10-3 mm2/s) of the spinal lesions. Through histological examination, a fibrocartilaginous embolism was definitively confirmed. This is the first report to describe an ischemic spinal injury visualized by DWI and ADC mapping with high-field MRI in a chondrodystrophic dog diagnosed with a fibrocartilaginous embolism.